Contemporary revolutions turning back to the future in 21st-century literature and art - Friedman, Susan Stanford 1943- (Bloomsbury Academic / Bloomsbury Publishing Plc, 2019)
"An exploration of how 21st-century writers, artists, and performers forge a new concept of contemporaneity, this book shows how their work re-purposes fiction, poetry, and paintings of the past. Returning to revolution's original meaning of 'cycle', Contemporary Revolutions examines how African, European, and Middle Eastern literature and the arts addresses the violence and inequities of the present. Friedman brings together essays on a broad range of artists and topics: artists including Kabe Wilson, fabric artist Ellen Bell, graphic designer Sana Yazigi; writers such as W. G. Sebald and poet Selina Tusitala Marsh and their reworking of authors Virginia Woolf and Albert Wendt; and traumatic occurrences from Nazism to the Syrian Revolution ...